Exploring Moral Value in Brianna and Bottomwise for Indonesian High School Teaching Material - Eka Karunianing Hapsari; Suparmin Suparmin; Titik Sudiatmi (Universitas Sebelas Maret, 2025)
The spread of issues regarding the morality of the younger generation, such as lack of manners, bullying, brawl and other juvenile delinquency is still a problem today, and a solution needs to be found immediately. An awareness of moral values can be done through literature and novels are one of the solutions. One novel that has good moral values in it is Brianna and Bottomwise by Andrea Hirata. In this novel, there are moral values that can be used as an example for the younger generation in their attitude, behavior and actions in everyday life. This study aims to describe the moral values aspect in terms of structural and extrinsic aspects in novels and its suitability as teaching material for Indonesian language subjects in high schools. This research used a descriptive qualitative design with a structural approach to analyze intrinsic elements such as themes and characters, and a moral approach by analyzing extrinsic values. Data were collected through close reading and note-taking techniques, then analyzed using triangulation. The results of the study reveal structural aspects of the novels Brianna and Bottomwise by Andrea Hirata are seen from the themes and characters. The manifestation of moral values in this novel; (1) the moral value of human relations with God, by praying to God and doing good deeds; (2) the moral value of the relationship between humans and the social environment, including helping each other, having good relationships with everyone, whether family or other people; (3) the moral values of human relations with themselves include never giving up, working hard and keeping promises. The findings of this study imply that Brianna and Bottomwise can be adapted into concrete learning media such as modules, student worksheets, and class discussions to strengthen character education. Wider implementation at various levels of education is also recommended so that literature-based learning can support national efforts to build students' moral character.